THE INTERPLAY OF NOSTALGIA AND MEMORABLE EXPERIENCES: A STUDY ON APPAREL - Albores, Alberto Borbolla; la Cruz, Salomón Domínguez; Reyes-Mercado, Pável (Jurnal Manajemen dan Kewirausahaan, 2024)
This study analyzed the relationship between nostalgia and memorable experiences on consumer purchase intention. While nostalgia was well-researched for Generation X and Y, there was a lack of understanding of how nostalgia influenced Generation Z brands and consumption preferences. Nostalgia marketing has been popular for several years, and there was literature on product and service categories, such as movie remakes, band reunions, candy, and brands that have completed their life cycle and could be re-released to the market by appealing to consumers nostalgia. It used a sample of 135 observations and sneakers stimuli advertising with nostalgic components. Results showed that nostalgia affected purchase intention directly and the retrieval of memorable experiences of using the apparel product. However, it did not translate to purchase intention. The results helped marketers identify courses of action to create effective communication that triggers consumers' purchase intention who did not require product development.